ACSA‐2 and GLAST classify subpopulations of multipotent and glial‐restricted cerebellar precursors. Issue 9 (31st May 2021) - Kantzer, Christina Geraldine; Parmigiani, Elena; Cerrato, Valentina; Tomiuk, Stefan; Knauel, Michail; Jungblut, Melanie; Buffo, Annalisa; Bosio, Andreas
Abstract: The formation of the cerebellum is highly coordinated to obtain its characteristic morphology and all cerebellar cell types. During mouse postnatal development, cerebellar progenitors with astroglial‐like characteristics generate mainly astrocytes and oligodendrocytes. However, a subset of astroglial‐like progenitors found in the prospective white matter (PWM) produces astroglia and interneurons. Characterizing these cerebellar astroglia‐like progenitors and distinguishing their developmental fates is still elusive. Here, we reveal that astrocyte cell surface antigen‐2 (ACSA‐2), lately identified as ATPase, Na+/K+ transporting, beta 2 polypeptide, is expressed by glial precursors throughout postnatal cerebellar development. In contrast to common astrocyte markers, ACSA‐2 appears on PWM cells but is absent on Bergmann glia (BG) precursors. In the adult cerebellum, ACSA‐2 is broadly expressed extending to velate astrocytes in the granular layer, white matter astrocytes, and to a lesser extent to BG. Cell transplantation and transcriptomic analysis revealed that marker staining discriminates two postnatal progenitor pools. One subset is defined by the co‐expression of ACSA‐2 and GLAST and the expression of markers typical of parenchymal astrocytes. These are PWM precursors that are exclusively gliogenic. They produce predominantly white matter and granular layer astrocytes. Another subset is constituted by GLAST positive/ACSA‐2 negative precursors that express neurogenic and BG‐like progenitor genes. This population displays multipotency and gives rise to interneurons besides all glial types, including BG. In conclusion, this work reports about ACSA‐2, a marker that in combination with GLAST enables for the discrimination and isolation of multipotent and glia‐committed progenitors, which generate different types of cerebellar astrocytes. Abstract : Glial cells of the cerebellum are still insufficiently classified. In this study we describe the subclassification of GLAST + precursors in the prospective white matter using immunophenotyping, transcriptomics, and transplantation assays. A subclass of GLAST + cells, which co‐express astrocyte cell surface antigen‐2 (ACSA‐2), generates only parenchymal astrocytes—as revealed by protein expression, their genetic signature and transplantation. The absence of the astrocyte marker (ACSA‐2) reveals GLAST + cells to maintain a multipotent potential, giving rise to interneurons, glia, and Bergmann glia.